L’étranger, le soldat et le bandit. Trois figures judiciaires du faux-monnayage hispanique transfrontalier à la fin du XVIIe siècle - Olivier Caporossi (Criminocorpus)
The foreigner, the demobilized soldier and the bandit are three main figures of the forgery Hispanic monnayage which pursue the courts of king Charles II (1665-1700) in the border spaces of Spain at the end of the XVIIth century. The defense of the monetary sovereignty of the last one of the Hapsburg obliged the royal justices to stigmatize the crimes monetary as the result of a long moral and social decay of the delinquent. It also implied the appointment of a guardian of the local judicial authorities by the council of Castile.